Computer-assisted management and control of manufacturing systems - Tzafestas, S.G (Advanced manufacturing series, 1997)
The pressure of increasing competition together with the development of new technologies has forced widespread changes in manufacturing methodologies. Present day manufacturers have to compete within international markets in addition to the local markets in which they previously operated. As a result manufacturing has had to abandon more traditional approaches and apply more suitable engineering and business techniques. State-of-the-art material on modern management and control methodologies is presented in this volume. Topics included are shop-floor scheduling, shop controller manager design, decision support, adaptive control, automatic supervision, balanced automation and collaborative manufacturing. This book's authoratative and experienced contributors examine important examples of modern manufacturing systems and provide techniques that are readily applicable in real situations. The reader should benefit from the style of the book which aims to imp rove analytical and design skills with the aim of operating efficient manufacturing systems.